Сравнительная морфология мышц свободного отдела грудной конечности подковоносов (Chiroptera, Rhinolophidae) - Ковтун, М.Ф. (Вестник зоологии, 1977)
The results are presented of studying the musculature of the thoracic limb free part in horseshoe bats of the USSR fauna. The musculature is described, weight of each muscle in comparison with total weight of all the muscles affecting the wing is given. A comparative analysis of these characters is presented for the studied species.